2021
DOI: 10.3390/jcm10132812
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Bilirubin Level with Metabolic Syndrome and Non-Alcoholic Fatty Liver Disease: A Cross-Sectional Study of 1672 Obese Children

Abstract: As in adults, obesity also plays a central role in the development of metabolic syndrome (MS) in children. Non-alcoholic fatty liver disease (NAFLD) is considered a manifestation of MS. Not only MS but also NAFLD seem to be inversely associated with serum bilirubin concentrations, an important endogenous tissue protector when only mild elevated. The aim of the study was to evaluate the association between serum bilirubin levels and the prevalence of MS and NAFLD in Italian obese children and adolescents. A ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 72 publications
1
12
0
Order By: Relevance
“…It has been reported repeatedly that individuals with Gilbert syndrome and increased bilirubin levels have a lower frequency of cardiovascular diseases, cancer, as well as various metabolic diseases compared to normobilirubinemic subjects [ 35 , 39 ]. However, as described above, the epidemiological data on the association of serum bilirubin and NAFLD/NASH reported so far are controversial [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. The results from our clinical study did not find any such association, as was similarly found in recently published studies [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported repeatedly that individuals with Gilbert syndrome and increased bilirubin levels have a lower frequency of cardiovascular diseases, cancer, as well as various metabolic diseases compared to normobilirubinemic subjects [ 35 , 39 ]. However, as described above, the epidemiological data on the association of serum bilirubin and NAFLD/NASH reported so far are controversial [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. The results from our clinical study did not find any such association, as was similarly found in recently published studies [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, as described above, the epidemiological data on the association of serum bilirubin and NAFLD/NASH reported so far are controversial [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. The results from our clinical study did not find any such association, as was similarly found in recently published studies [ 22 , 23 , 24 , 25 , 26 ]. The major confounding factor might be NAFLD-induced liver dysfunction, which might even lead to a certain elevation of serum bilirubin concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, large amounts of data have been obtained from several observational epidemiological studies, whereas there is a lack of controlled clinical trials offering the highest clinical evidence. Second, a recent large retrospective cross-sectional study on severely obese children showed that bilirubin is inversely associated only with some components of MetS, such as high blood pressure, high triglycerides, waist circumference, waist–height ratio, CRP levels, and HOMA-IR index; interestingly, no association between serum bilirubin and MetS or fatty liver was found [ 131 ]. This study showed that bilirubin is not protective in the presence of severe obesity (BMI > 95th percentile), whereas there is a greater number of published studies focused on the whole spectrum of individuals from overweight to obese.…”
Section: Prospective Practice Of Bilirubin Regulation In Obesity Treatmentmentioning
confidence: 99%
“…Both MetS and NAFLD seem to be associated with serum bilirubin, including total bilirubin (TBIL), DBIL, and IBIL. And the increase in bilirubin levels has been demonstrated to be negatively correlated with the prevalence of NAFLD (8,(13)(14)(15)(16). Nevertheless, the alternative study based on Mendelian randomization analysis did not find a causal relationship between bilirubin levels and the risk of NAFLD (17,18).…”
Section: Introductionmentioning
confidence: 99%